Origin of domain wall induced magnetoelectricity in rare-earth iron garnet single crystals and films. (12th March 2017) - Popov, A. I.; Gareeva, Z. V.; Zvezdin, A. K.; Gareev, T. T.; Sergeev, A. S.; Pyatakov, A. P.
ABSTRACT: In this article, we discuss the mechanism of magnetoelectric effect in rare-earth iron garnets related to the low symmetry environment of rare-earth ions and magnetic inhomogeneity created by iron subsystem. Low symmetry environment of rare-earth ions leads to antiferroelectric arrangement of their electric dipole moments and favors releasing of iron garnets ferroelectricity. Magnetic domain walls act as the sources of non-uniform effective magnetic field breaking antiferroelectric ordering. We calculate electric polarization in a vicinity of Bloch domain walls in rare-earth iron garnet crystals and films, pick out their distinguished features, and touch upon experimental evidences of domain wall induced magnetoelectricity.